Autism spectrum disorder related to unwarranted paracetamol use in pregnancy: letter to the editor - Asmat Zehra; Gul-e-Zehra; Hina Altaf (Journal of the Pakistan Medical Association, 2022)
Dear Editor, There has been a rapid increase in self-medication with over-the-counter (OTC) drugs, mostly paracetamol, by pregnant women lately. [1,2] Its rampant use is due to easy availability and cost-effectiveness. Pregnant women mostly self-medicate for nausea, vomiting, backache and fever. [A study from Pakistan reported OTC drug use by 37.9% of pregnant women, whereas 77.4% of them were unaware of its indications, dosages and potential hazards. Their use of OTC drugs was based on the experience or recommendations of relatives and pharmacists. [1] This unchecked use of paracetamol can be dangerous in pregnancy because its metabolites cross the placenta and blood-brain barrier of the fetus readily and pose significant risk to the normal neurodevelopment of the fetus, by interfering with the immunologic development of the brain. [2] —Continue